Perbandingan Kualitas Suara Smartphone Menggunakan Metode Dynamic Time Warping (DTW) - Inas Salsabila; Samsul Anwar; Radhiah Radhiah (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Smartphones are telecommunication devices that play a significant role in daily life. The sound quality produced by a smartphone becomes important for users, considering that poor sound quality might cause misunderstandings in communication. This study provides an illustration of the application of Dynamic Time Warping (DTW) in the comparison of the sound quality produced by a smartphone. In addition to the DTW, the median test and its confidence interval are also used to determine the sound quality of a smartphone. The data employed are primary data in the form of voice recordings of six people that saying five sample sentences, each of which is repeated five times through four different smartphone types that are used as examples. So that the total voice recordings for each smartphone are 150 pieces. This study aims to compare the sound quality produced by those smartphones. The results of this study indicate that although smartphones type 2, 3 and 4 have similar sound quality, the sound quality produced by smartphones type 4 is more stable than other types. Therefore, this study concludes the smartphone type 4 is the smartphone with the most satisfying sound quality. Furthermore, this study showed that the DTW method is effective in analyzing the sound quality of a smartphone.